Alterations of Membrane Lipid Content Correlated With Chloroplast and Mitochondria Development in Euglena gracilis - Shibata, Shiori; Arimura, Shin-ichi; Ishikawa, Takahiro; Awai, Koichiro (Frontiers in Plant Science, 2018)
Euglenoids are unique protists that can grow photoautotrophically, photomixotrophically, and heterotrophically. Here we grew Euglena gracilis under these different growth conditions and determined cellular contents of seven membrane lipids and one storage lipid (triacylglycerol), which account for more than 94 mol% of total membrane lipids. We also describe the relationship among chloroplast and mitochondria developments with lipid contents, protein contents, and oxygen evolution/consumption rates. In photoautotrophic growth conditions, E. gracilis cells accumulated chlorophyll, photosynthetic proteins, and glycolipids typical to thylakoid membranes. The same occurred for the cells grown under photomixotrophic conditions with higher respiration rates. In heterotrophic conditions, E. gracilis cells had higher respiration rates compared to cells grown in other conditions with the accumulation of pyruvate: NADP+ oxidoreductase, a mitochondrial protein and phospholipid common in mitochondria. Cells were also observed using a confocal laser scanning microscope and found to show more chlorophyll autofluorescence when grown photoautotrophically and photomixotrophycally, and fluorescence of MitoTracker when grown photomixotrophically and heterotrophically. These results suggest that under illumination, E. gracilis develops functional thylakoid membranes with membrane lipids and proteins for photosynthesis. In the medium with glucose, the cells develop mitochondria with phospholipids and proteins for respiration. Possible application based on lipid analysis for the enhancement of wax ester or alkene synthesis is discussed.